4 APPEASEMENT AND WAR. (July 2022) - Unknown
Abstract : Lothian on his meeting with Adolf Hitler. Many thanks for sending me the book of Letters which I am delighted to have. I had an interesting time with Hitler. It is going to be a difficult job but I think it is possible to get a basis for assured peace in Europe for ten years if we go about it the right way.